Honestly man i don’t know Im in 6th grade bro
Answer:
h(3) = - 140
Step-by-step explanation:
Generate the terms in the sequence by substituting n = 2 and 3 into h(n)
h(2) = h(2 - 1) × 2 = h(1) × 2 = - 35 × 2 = - 70
h(3) = h(3 - 1) × 2 = h(2) × 2 = - 70 × 2 = - 140
Answer:
Step-by-step explanation:
The answer is 180.add 40 to its self or multiply by 4 then add 20 for the .5 portion, 40x4=160 160+20=180.
hoped this helped =)
Answer:
Step-by-step explanation:
-6x²+15x+9=0
divide by -3
2x²-5x-3=0
2x²+x-6x-3=0
x(2x+1)-3(2x+1)=0
(2x+1)(x-3)=0
either x=-1/2
or x=3